Research methods for graduate business and social science students - Adams, John, 1955- (New Delhi ; Response Books ; Thousand Oaks, Calif. : SAGE Publications, 2007)
"Research Methods for Graduate Business and Social Science Students is a fundamental and easy guide to studying research methods. In addition to general concepts relating to research methods, broad research issues and theoretical concepts critical to research are discussed. The book is written in a lucid style and contains examples and helpful practical exercises at the end of each chapter to reinforce and enjoy learning. Divided Into 16 chapters, the authors aim to clearly and concisely explain the basics of quantitative and qualitative analysis and research to students."--Jacket.
Sect. I. General introduction -- Ch. 1. Introduction to research -- Sect. II. Research methodology -- Ch. 2. Research methodology -- Sect. III. Formulation -- Ch. 3. The research cycle -- Ch. 4. Literature Review and critical reading -- Sect. IV. Research design -- Ch. 5. Sampling -- Sect. V. Data collection -- Ch. 6. Primary data collection -- Ch. 7. Secondary data collection -- Ch. 8. Surveys -- Ch. 9. Interviews -- Sect. VI. Analysis -- Ch. 10. Qualitative data analysis -- Ch. 11. Descriptive quantitative analysis -- Ch. 12. Correlation and regression -- Ch. 13. Advanced statistical analysis -- Sect. VII. Quality and verification -- Ch. 14. Tests of measurement and quality -- Sect. VIII. Involvement during research -- Ch. 15. Conducting your research -- Ch. 16. Writing and presenting the dissertation.
Includes bibliographical references and index.
Keywords: Social sciences -- Research; Social sciences -- Methodology